2011
DOI: 10.1021/ma200846v
|View full text |Cite
|
Sign up to set email alerts
|

End Group-Functionalization and Synthesis of Block-Copolythiophenes by Modified Nickel Initiators

Abstract: Polythiophenes with alcohol, tosylate, azide, ethynylene, carboxylic acid and amine end groups were prepared by a combination of functionalized nickel initiators and post-polymerization reactions. The azide and ethynylene polymers were subsequently used in a click reaction to produce a conjugated block-copolymer. Finally, a conjugated triblock-copolymer was synthesized by means of a chain growth polymerization initiated by a binuclear nickel initiator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 44 publications
0
64
0
Order By: Relevance
“…In the solubility‐limited region, the molecular weights are limited by the solubility of the copolymer, which depends on its composition. Koeckelberghs and co‐workers also reported that the catalyst dissociates from the polymer backbone and that the number of propagations that occur before dissociation depends on the molar ratio of 3HOT monomer …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the solubility‐limited region, the molecular weights are limited by the solubility of the copolymer, which depends on its composition. Koeckelberghs and co‐workers also reported that the catalyst dissociates from the polymer backbone and that the number of propagations that occur before dissociation depends on the molar ratio of 3HOT monomer …”
Section: Resultsmentioning
confidence: 99%
“…However, no systematic study has been made by varying the monomer composition between alkyl and alkoxy side chains in the polythiophenes. In addition, Koeckelberghs and co‐workers reported the effect of the transfer of supramolecular chirality in block copolymers of P3HT and P3AOT, and studied the synthesis of P3HT‐ block ‐poly[3‐(3,7‐( S )‐dimethyloctyloxy)thiophene] with different spacers . However, the synthesis of random copolymers with different monomer units using the GRIM method is challenging since it has been shown that the success of catalyst‐transfer polymerization depends strongly on the monomer reactivity ratio …”
Section: Introductionmentioning
confidence: 99%
“…In order to get more information on the intrinsic reasons leading to the failure of the polymerization reaction, an external initiator [32][33][34] was used, since end-group analysis of the resulting polymers/oligomers through MALDI MS is likely to help identifying undesired side-reactions. 35,36 This initiator (Fig.…”
Section: Synthesis Of the Polymers Using External Initiatormentioning
confidence: 99%
“…1-(5-hexyn-1-yl)-1′-methyl-4,4′-bipyridinium dihexafl uorophosphate (21.7 mg, 0.04 mmol) and azide terminal PEG [200 mg, 0.04 mmol, M w = 5 kDa] were dissolved in dimethyl sulphoxide (0.4 mL) and the solution purged with N 2 for 1 h. The Cu(CH 3 CN) 4 PF 6 (14.9 mg, 39.9 μ mol) was then added and the reaction mixture heated to 60 °C overnight. The polymer was then precipitated from diethyl ether (45 mL) to yield an off white solid.…”
Section: Viologen Terminal Peg (3)mentioning
confidence: 99%
“…Control of end-group functionality is critical for a wide range of macromolecular associations ranging from the formation of diblock copolymers, [1][2][3] including conjugated polymer [ 4 ] to bioconjugates for drug delivery. [5][6][7] High endgroup fi delity is equally important in surface modifi cation, for example, for nanoparticle functionalization and the understanding of biosynthesis.…”
Section: Introductionmentioning
confidence: 99%